Applications of ultrasensitive wavelength‐modulated differential photothermal radiometry to noninvasive glucose detection in blood serum. Issue 11 (29th August 2012) - Guo, Xinxin; Mandelis, Andreas; Zinman, Bernard
Abstract Wavelength‐Modulated Differential Laser Photothermal Radiometry (WM‐DPTR) has been designed for noninvasive glucose measurements in the mid‐infrared (MIR) range. Glucose measurements in human blood serum in the physiological range (20–320 mg/dl) with predicted error <10.3 mg/dl demonstrated high sensitivity and accuracy to meet wide clinical detection requirements, ranging from hypoglycemia to hyperglycemia. The glucose sensitivity and specificity of WM‐DPTR stem from the subtraction of the simultaneously measured signals from two excitation laser beams at wavelengths near the peak and the baseline of the strongest interference‐free glucose absorption band in the MIR range. It was found that the serum glucose sensitivity and measurement precision strongly depend on the tunability and stability of the intensity ratio and the phase shift of the two laser beams. This level of accuracy was favorably compared to other MIR techniques. WM‐DPTR has shown excellent potential to be developed into a clinically viable noninvasive glucose biosensor. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)